Analisis Sistem Pembiayaan Akad Qardhul Hasan Di BMT Al-Amanah Cabang Subang - Meinizar Arini Putri; Siti Hapipah; Siti Rohmat (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
The Qardhul Hasan financing at BMT Al-Amanah Subang was not surveyed again, because the Qardhul Hasan survey had been carried out at the beginning of the members doing previous financing such as Mudharabah, Murabahah, Musyarakah, and Rahn financing, because Qarhdul Hasan financing is a conversion from the previous contract. Qardhul Hasan financing has certain categories for financing the needs of members such as education costs, medical expenses, and so on. The purpose of this study was to determine the terms and conditions of financing Qardhul Hasan at BMT Al-Amanah Subang Branch; To find out the Qardhul Hasan contract financing system at BMT Al-Amanah Subang Branch; and To find out the benefits of the Qardhul Hasan Agreement for members and managers of BMT Al-Amanah Subang Branch. The results of this study 1). The terms and conditions of Qardhul Hasan financing at BMT Al-Amanah Subang Branch do not use collateral on the condition that they must become members of BMT Al-Amanah, and members are no longer able to pay installments of previous contract financing that have matured; 2. Qardhul Hasan Financing System at BMT Al-Amanah Subang Branch, namely: a). For members of BMT Al-Amanah who are active members by having principal and mandatory savings, b). For members who already have financing, which is past due, but have difficulty paying the financing installments, BMT Al-Amanah converts the contract into Qardhul Hasan; 3). The benefits of Qardhul hasan for members and managers are: a). For members, it is very helpful for members who are having difficulty paying installments and as a source of non-commercial loans / bailout funds, b). For managers, namely because Qardhul Hasan financing is social and please help it will give a good image for BMT Al-Amanah Subang Branch.